Multi-omics of in vitro aortic valve calcification - Semenova, Daria; Zabirnyk, Arsenii; Lobov, Arseniy; Boyarskaya, Nadezda; Kachanova, Olga; Uspensky, Vladimir; Zainullina, Bozhana; Denisov, Evgeny; Gerashchenko, Tatiana; Kvitting, John-Peder Escobar; Kaljusto, Mari-Liis; Thiede, Bernd; et al. (Frontiers in Cardiovascular Medicine, 2022)
Heart valve calcification is an active cellular and molecular process that partly remains unknown. Osteogenic differentiation of valve interstitial cells (VIC) is a central mechanism in calcific aortic valve disease (CAVD). Studying mechanisms in CAVD progression is clearly needed. In this study, we compared molecular mechanisms of osteogenic differentiation of human VIC isolated from healthy donors or patients with CAVD by RNA-seq transcriptomics in early timepoint (48 h) and by shotgun proteomics at later timepoint (10th day). Bioinformatic analysis revealed genes and pathways involved in the regulation of VIC osteogenic differentiation. We found a high amount of stage-specific differentially expressed genes and good accordance between transcriptomic and proteomic data. Functional annotation of differentially expressed proteins revealed that osteogenic differentiation of VIC involved many signaling cascades such as: PI3K-Akt, MAPK, Ras, TNF signaling pathways. Wnt, FoxO, and HIF-1 signaling pathways were modulated only at the early timepoint and thus probably involved in the commitment of VIC to osteogenic differentiation. We also observed a significant shift of some metabolic pathways in the early stage of VIC osteogenic differentiation. Lentiviral overexpression of one of the most upregulated genes (ZBTB16, PLZF) increased calcification of VIC after osteogenic stimulation. Analysis with qPCR and shotgun proteomics suggested a proosteogenic role of ZBTB16 in the early stages of osteogenic differentiation.